Az ötféle jószág terminológiája a mongol nyelvekben - Gombkötő Bence (Móra Akadémia, 2023)
The traditional lifestyle of the Mongols is nomadic pastoralism, in which livestock are herded to seek fresh pastures on which to graze. These animals are often referred to as the “five animals” or “five kinds of livestock” in Mongolian. These are the horse, the camel, the horned cattle, the sheep, and the goat. The vocabulary of these animals has several unique linguistic and cultural features. Each of them has a specific term according to their age and sex. For the pastors, it is important to express accurately the age and the sex for the breeding and selection. Besides that, the terminology of domestic animals in Mongolic has a large number of Turkic loanwords, which show a significant linguistic and cultural influence. The author will attempt to show the terminology of the five animals and highlight their appearance in the different Modern Mongolic languages and their origin.